Experimental and analytical investigation on CFRP strengthened glulam laminated timber beams: Full-scale experiments. (1st May 2019) - Vahedian, Abbas; Shrestha, Rijun; Crews, Keith
Abstract: Timber is one of the most appealing and aesthetic construction materials with excellent characteristics compared with other construction materials such as steel, concrete and clay bricks. It is one of the oldest sustainable construction materials and still continues to be a popular choice in modern infrastructure. In recent years, fibre reinforced polymers (FRP) has emerged to improve mechanical properties even further. In this study, results of experimental tests on strengthened glulam beams have been used to investigate potential parameters affecting flexural strength and ultimate load carrying capacity of glulam beams strengthened with externally bonded FRP sheets. Eight full-scale timber beams with and without FRP reinforcement were tested where the bonded length, width, and thickness of the FRP was varied for FRP strengthened beams. The test results pointed out that reduction of stress concentrations can enhance the mechanical performance of the strengthened beams. The ultimate load carrying capacity and flexural strength of reinforced beams improved significantly when bond length and bond width increased. Results of experiments showed that further increase in bond thickness predominantly improves stiffness and ductility of the strengthened timber beams which has a significant enhancement in ultimate deflection and serviceability limit state. An analytical model has been established to determine the ultimate flexural capacity of strengthened timber beam. Satisfactory correlation is achieved between measured and predicted flexural capacity, signifying the capability of the new models.